Real‐world use of inhaled treprostinil for lung disease‐pulmonary hypertension: A protocol for patient evaluation and prescribing. (7th September 2022) - Johnson, Shelsey W.; Finlay, Lauren; Mathai, Stephen C.; Goldstein, Ronald H.; Maron, Bradley A.
Abstract: Inhaled treprostinil was approved recently for interstitial lung disease‐pulmonary hypertension; however, efficacy in "real‐world" populations is not known. We designed a protocol and report our experience evaluating 10 patients referred for therapy. Misdiagnosis at presentation was common; ultimately, three patients (30%) were prescribed drug. This protocol offers an opportunity to standardize longitudinal assessment of inhaled treprostinil in clinical practice.